OBJEKTIFIKASI PEREMPUAN DAN TUBUH: WACANA TUBUH PEREMPUAN DALAM LIRIK LAGU DANGDUT POPULER TAHUN 2000-2013 - Rima Firdaus Lahdji (Universitas Airlangga, 2015)
This research aims to (1) to find women body construction on popular dangdut stories on 2000-2013 and (2) to understand the meaning and discourse on popular dangdut stories on 2000-2013. This study applied Sara Mills discourse analysis which focuses on subject-object position, audience position and gender on the texts.This research uses qualitative-descriptive methods and aims to understand phenomena, discourse and description which is shown by words and language on popular dangdut stories. The result of this research shows women body on dangdut stories become viewing objects and sexual objects. Popular dangdut stories from 2000-2013 shows that women still become second position and object for men. The changing and shifting on women body construction can’t be released from men position and domination. As object viewing, parts of women body which constructed are hip and butt. Meanwhile, as sexual object, parts of women body which constructed are “vagina” with neglecting of virginity. Even though, ideology and discourse on dangdut stories also served as a mechanism to explain the involvement of women on the oppression of themselves.